Genetic diversity in natural populations of Piper cernuum - Mariot, A.; Di Stasi, L. C.; dos Reis, M. S. (Oxford University Press, 2002)
Piper cernuum is a native plant of the Brazilian Atlantic rain forest. This work studies the distribution of allozyme diversity in P. cernuum natural populations in order to establish a strategy for sustainable management and conservation. Leaf samples were collected in two Brazilian states. High divergences among populations (F-SR = 0.380) and low divergences among regions (F-RT = -0.069) and among gaps of the same population (F-GT = 0.062) were found. No association between the geographical variation and the genetic distance was detected. An excess of heterozygotes was detected in the populations (F-IS = -0.170), suggesting selection in favor of heterozygotes. The results, and the fact that the species depends on constant gap formation for maintenance of its dynamism, suggest that the founder effect is largely responsible for the structuring of populations. For sustainable management, the maintenance of plants/reproductive branches in the gaps is of major importance. The genotypes produced in these gaps are responsible for the establishment of new gaps and are the foundation for new populations, maintaining the dynamics of allele movement.